Plate Tectonics and Northern Cordilleran Geology: An Unfinished Revolution - Monger, J. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary The northern Cordillera, located on a continent-ocean interface in existence for 750 million years, is an orogenic collage mostly made up of Paleozoic through early Mesozoic intraoceanic arc and subduction complex terranes accreted to the craton margin, and mid-Mesozoic to Holocene arc semplaced mainly in and on the accreted terranes. Mountain building results from crustal thickening most likely caused by persistent movement of the North American plate towards, and over, various Pacific oceanic plates since Early Jurassictime. Location of collage components intime and space is needed to show the succession of plate configurations that led to the collage, but current conflict between estimates of amounts of lateral displacements means that pre-Tertiary paleogeographies remain in doubt.